Response planning in word typing: Evidence for inhibition. (22nd October 2014) - Pinet, Svetlana; Hamamé, Carlos M.; Longcamp, Marieke; Vidal, Franck; Alario, F.‐Xavier
Abstract: Typing is a pervasive phenomenon, yet the underlying neural processes have hardly been studied. Here, the mechanisms of keystroke preparation were studied with a typed picture‐naming task performed by expert typists. Electroencephalographic activities recorded over sensorimotor areas prior to first‐keystroke onset were examined with time‐frequency and event‐related potential (ERP) analyses. In the time‐frequency domain, a beta event‐related desynchronization was present bilaterally. In the ERP analyses, the activity was asymmetric, with negativity and positivity patterns developing over, respectively, contra‐ and ipsilateral recording sites. This pattern is similar to that observed in choice reaction time tasks, and thus can be interpreted as evidence of contralateral motor cortex activation accompanied by inhibition of the ipsilateral motor cortex. These data constitute the first electrophysiological demonstration of inhibitory activity in typing and pave the way to a thorough study of typing.